Effect of Reflective-Reciprocal Teaching Strategies on Pre-Service Teachers’ Achievement in Integrated Science and Science Process Skills in Nigerian Colleges of Education (2013)
The low level of performance of pre-service teachers in Integrated Science has been a recurrent problem in science education. Poor instructional strategies employed by lecturers in colleges of education have been adduced as one of the reasons for this low level of performance in Integrated Science. Previous researches have focused on collaborative teaching and self-regulation strategy without considering opportunity for reflection before, during and after lessons which the Reflective-Reciprocal Peer Tutoring (RRPT) addresses. This study, therefore, determined the effect of Reflective-Reciprocal Teaching (RRT) and Reflective-Reciprocal Peer Tutoring strategies on pre-service science teachers‟ achievement in Integrated Science and Science Process Skills. It also determined the moderating effect of mode of entry and numerical ability on the dependent variables. The pretest-posttest, control group, quasi experimental design with a 3x3x2 factorial matrix was used. Three colleges of education were purposively selected from each of the state and federal colleges in Southwestern Nigeria. One intact class of Nigeria Certificate in Education year two was selected from each of the six colleges making a total of 295 pre-service teachers. Six instruments were developed, namely: Pre-service Teachers‟ Achievement Test (r= 0.85); Pre-Service Teachers‟ Science Process Skills Rating Scale (r=0.82), Pre-Service Teachers‟ Numerical Ability Test (r=0.79); Operational Guides for RRT, RRPT and Modified Conventional Teaching Strategy (r=0.75, 0.72 and 0.77 respectively). Seven hypotheses were tested at 0.05 level of significance. Data were subjected to Analysis of Covariance and Scheffé Post-hoc test. Treatment had a significant effect on pre-service teachers‟ achievement in Integrated Science (F(2,276) = 56.15; p<.05) and science process skills (F(2,276) = 33.53; p< 0.05), Pre-service teachers exposed to RRPT obtained a higher achievement score (x=24.8) than those in the RRT ( x = 21.02) and control group ( x = 18.89). For Science Process skills, the RRT group had a higher achievement score ( x = 57.50) than those in the RRPT ( x = 49.28) and control (x = 47.04) groups. Mode of entry and numerical ability had no significant effect on pre-service teachers‟ achievement in Integrated Science and science process skills. The interaction effects of treatment and mode of entry, treatment and numerical ability, as well as the interaction effect of treatment, mode of entry and numerical ability on pre-service teachers‟ achievement in Integrated Science and science process skills were not significant.The Reflective-Reciprocal Teaching and Reflective-Reciprocal Peer Tutoring strategies enhanced pre-service science teachers‟ achievement in Integrated Science and science process skills. When employed by the teachers of the subject, the two strategies could help pre-service Integrated Science teachers to gain more in achievement and science process skills, enhance their professional development and encourage social interaction in the learning environment. These strategies are therefore, recommended for teaching Integrated Science at the college of education level.